PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT INFRACOM TECHNOLOGY JAKARTA PUSAT - Yesica Chrismarelda; Siska Yunanti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the effect of organizational culture and work discipline on employee performance at PT Infracom Technology in Central Jakarta. The background of this study stems from suboptimal employee performance and the company's failure to achieve its targets. The type of research used was quantitative research with an associative method. The sample in this study was 96 employees of PT Infracom Technology, Central Jakarta. Data collection techniques were carried out by distributing questionnaires using a Likert scale, while data analysis was performed using SPSS version 26, which included validity tests, reliability tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The results show that the organizational culture variable (X1) has a positive and significant effect on employee performance, with a t-value of 8.578 > t-table = 1.986 and significance of 0.000 < 0.05. The work discipline variable (X2) also has a positive and significant effect on employee performance, with a t-value of 11.702 > t-table = 1.986 and significance of 0.000 < 0.05. Simultaneously, both variables have a significant effect on employee performance with a calculated F value = 104.784 > table F = 3.090 and significance 0.000 < 0.05. The coefficient of determination value of 69.3% shows that organizational culture and work discipline contribute to improving employee performance, while the remaining 30.7% is influenced by other factors. The results of this study emphasize the importance of a conducive organizational culture and work discipline in improving employee performance at PT Infracom Technology, Central Jakarta.